Sustained hippocampal neural plasticity questions the reproducibility of an amyloid-β-induced Alzheimer’s disease model - Paulo, Sara L (2021)
Background: The use of Alzheimer's disease (AD) models obtained by intracerebral infusion of amyloid-β (Aβ) has been increasingly reported in recent years. Nonetheless, these models may present important challenges. Objective: We have focused on canonical mechanisms of hippocampal-related neural plasticity to characterize a rat model obtained by an intracerebroventricular (icv) injection of soluble amyloid-β42 (Aβ42). Methods: Animal behavior was evaluated in the elevated plus maze, Y-Maze spontaneous or forced alternation, Morris water maze, and open field, starting 2 weeks post-Aβ42 infusion. Hippocampal neurogenesis was assessed 3 weeks after Aβ42 injection. Aβ deposition, tropomyosin receptor kinase B levels, and neuroinflammation were appraised at 3 and 14 days post-Aβ42 administration. Results: We found that immature neuronal dendritic morphology was abnormally enhanced, but proliferation and neuronal differentiation in the dentate gyrus was conserved one month after Aβ42 injection. Surprisingly, animal behavior did not reveal changes in cognitive performance nor in locomotor and anxious-related activity. Brain-derived neurotrophic factor related-signaling was also unchanged at 3 and 14 days post-Aβ icv injection. Likewise, astrocytic and microglial markers of neuroinflammation in the hippocampus were unaltered in these time points. Conclusion: Taken together, our data emphasize a high variability and lack of behavioral reproducibility associated with these Aβ injection-based models, as well as the need for its further optimization, aiming at addressing the gap between preclinical AD models and the human disorder.